Consensus document APAIR: atopic dermatitis in children — update 2019 (short version) Part 1. - Yu. S. Smolkin; I. I. Balabolkin; I. A. Gorlanov; L. S. Kruglova; A. V. Kudryavtseva; R. Y. Meshkova; H. B. Migacheva; R. F. Khakimova; A. A. Cheburkin; E. A. Kuropatnikova; N. A. Lyan; A. V. Maksimova; et al. (Аллергология и Иммунология в Педиатрии)
Atopic  eczema (atopic dermatitis, AD) — chronic recurrent  inflammation of the skin, arising as a result of a violation of the epidermal barrier and  entailing its further dysfunction. Maximum development atopic  dermatitis reaches  on the background of predisposition to IgE-mediated hypersensitivity, implemented in sensitization to surrounding allergens.The diagnosis  of  atopic  eczema  is clinical.  An  obligatory clinical  symptom is itching  in combination with  3 other criteria: typical morphology and distribution; a history of atopy; chronically xerosis; AD debut  up to 2 years. The phase of the disease and the severity of skin lesions are of practical  importance for clarifying the stage AD. Changes  characteristic of different phases can be observed  simultaneously. Morphological and age-related classifications of AD are conditional and have little effect on the therapeutic strategy. Clinical variants of AD (allergic and non-allergic) are a single nosological form that requires  common  approaches to therapy. The prevalence of AD  is greatest  in children  a 1-st  year  of life  (up  to 30%) and significantly decreases  in adolescence.Point and inherited mutations in genes (for  example, filaggrin) are a key point  in the pathogenesis of AD. Immune disorders are not limited  to IgE-dependent reactions  and occur with the participation of many cytokines (IL-4, IL-5,  IL-13, IL-25, IL-31, TSLP). Bacteria and fungi act as infectious agents  or superantigens for lymphocytes.Food allergies are detected in 30–40% of children with AD causing aggravation of the disease. The children in the first year dominated by sensitization to food  allergens: milk, eggs, cereals, fish. An allergological examination using skin prick tests or specific IgE is informative and necessary, but the presence  of sensitization should  be clarified using an elimination-provocation  test with this product.